1986
DOI: 10.1121/1.393228
|View full text |Cite
|
Sign up to set email alerts
|

Methods of measuring the attenuation of hearing protection devices

Abstract: The published literature describing three real-ear-attenuation-at-threshold (REAT), nine above-threshold, and four objective methods of measuring hearing protector attenuation is reviewed and analyzed with regard to the accuracy, practicality, and applicability of the various techniques. The analysis indicates that the REAT method is one of the most accurate available techniques since it assesses all of the sound paths to the occluded ear and, depending upon the experimenter's intention, can reflect actual in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 24 publications
3
76
0
1
Order By: Relevance
“…At present, the earmuff usage time is estimated to be 79 070 for forest workers and 93 % for shipyard workers. The attenuation of earmuffs under work conditions is not well known (2,6,10,15). In this study it was measured with a miniature microphone method with an estimated error of only ± 2 dB in frequency response, due to the positioning of the microphone close to the ear canal entrance (4, 6, 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, the earmuff usage time is estimated to be 79 070 for forest workers and 93 % for shipyard workers. The attenuation of earmuffs under work conditions is not well known (2,6,10,15). In this study it was measured with a miniature microphone method with an estimated error of only ± 2 dB in frequency response, due to the positioning of the microphone close to the ear canal entrance (4, 6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Our aim was to evaluate the noise level at the external ear in accordance with Robinson's immission level. The sound pressure at the eardrum could be calculated from the noise reduction by the open ear transfer function (6). • ," :…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive reviews of measurement methods commonly used to evaluate the attenuation performance of hearing protection devices (HPD) can be found in the literature [1]- [5]. These methods are usually divided into two categories: subjective and objective methods.…”
Section: Introductionmentioning
confidence: 99%
“…Music is characterized by complex spectral characteristics, most of which are concentrated in the low frequencies (i.e., <100 Hz). Research has shown that the REAT procedure has known limitations for accurately assessing occluded perception of frequencies below 500 Hz, due to masking by physiological noise [15].…”
Section: Introductionmentioning
confidence: 99%